(untitled) (Revista Argentina de Cirugía, 2021)
Necrotizing soft tissue infection (NSTI) is a rare disease that mainly affects individuals with specific risk factors but sometimes affects postpartum women as well. These women have a state of immunosuppression, which would favor the appearance and more aggressive course of the disease. We report the case of a 20-year-old woman with no pathological history who developed necrotizing fasciitis of the abdominal wall as a complication of a cesarean section. An extensive abdominal wall resection was performed, followed by total histerectomy and bilateral adnexectomy, peritoneal cavity lavage, and temporary abdominal closure with a Bogotá bag. After prolonged hospitalization in an intensive care unit, the abdominal wall was closed using a polyglactin mesh in contact with the viscera, on which a polypropylene mesh was placed to provide resistance. Negative pressure wound therapy with a Barker´s vacuum pack was started until the reconstruction of the abdominal wall with autologous skin grafts could be programmed. Then, a V.A.C. ATS ® therapy was used on skin grafts, showing a favorable evolution. The objective of this scientific letter is to discuss an uncommon complication of the cesarean section, emphasizing the most important aspects of the disease, and defining recommendations for the management of this pathology and its multidisciplinary approach.